STUDYING THE EVOLUTIONARY STAGES OF TRANSLATION THEORY - Shadiyeva, Shahnoza (Журнал иностранных языков и лингвистики, 2023)
Our article examines the topic of translation science of translation practice, its specifics, history, principles, principles and principles, considers the choice of work to become a translator, linguistic differences and other features inherent in the original, works that provide practical help in carrying from works taking into account national literary traditions.